ANALYSIS OF THE IMPACT OF FUEL PRICE INCREASES ON THE PURCHASING POWER OF THE COMMUNITY IN DEPOK CITY (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
This study aims to determine how the increase in non-subsidized fuel prices affects the ability of the people of Depok City to purchase goods and services. This research employs a quantitative descriptive method using simple linear regression analysis, with data processed using SPSS software version 26. The sampling technique used was non-probability sampling with the accidental sampling type, involving a total sample of 114 respondents from the Depok City community who experienced the impact of the non-subsidized fuel price increase. The validity and reliability test results indicate that all statement items for both variables are considered valid and reliable, with Cronbach's Alpha values reaching 0.933 for the fuel price increase variable (X) and 0.921 for the community purchasing power variable (Y). The simple linear regression analysis produced the equation Y = 7.255 + 0.918X. The significance value obtained was 0.000, which is smaller than 0.05. In addition, the calculated t-value of 12.462 is greater than the t-table value of 1.981. Thus, it can be concluded that the increase in fuel prices has a positive and significant effect on community purchasing power. The R² value of 0.581 indicates that the fuel price increase can explain 58.1% of the change in community purchasing power, while the remaining 41.9% is influenced by factors outside the scope of this study. The findings of this study indicate that policies are needed to mitigate the impact, such as providing appropriate social assistance to communities significantly affected by the rise in fuel prices.